HIV- A Hidden Pandemic Burdening Healthcare Globally - Maheshwari, Chanchal; Khan, Shehroz; Hussain, Iqra Faraz; Qasim, Muhammad Zohaib (Archives of Clinical and Medical Case Reports, 2024)
HIV is a global burden causing mortality and morbidity, we write to highlight the constant HIV incidence, its misdiagnosis and associated factors causing lack of eradication despite being an actively targeted disease worldwide utilizing US 20-29 billion per year. From the pandemics aggravating immunosuppression to the revolution of the world through increased practice of homosexuality, multiple partners and drug abuse, major concern of HIV is more than ever.